Rekrutmen Calon Kepala Daerah Partai Demokrasi Indonesia Perjuangan Di Kabupaten Minahasa Utara - Pangemanan, Melky J; Liando, Daud M; Lengkong, Johny (JURNAL ILMIAH SOCIETY, 2016)
A political party is one of the pillars of democracy and political means to facilitate the political elite in order to achieve a power. Political parties as a container dealer aspirations of the people is expected in the effort to build democracy procedural even the goal with a substantial build democracy. Recruitment is one of the functions of political parties to select figures who have the willingness to participate actively in politics and have the potential to establish a political party and to dedicate themselves to the development of the nation. Recruitment is on the approach to capture political party members and cadres to fight for the partys vision and mission to actualize roles to fill public office gradually and selectively. This study aims to analyze the processes and mechanisms undertaken by the Indonesian Democratic Party of Struggle in determining candidates for regional head in North Minahasa Regency. This study used a qualitative approach. It can be concluded from the Indonesian Democratic Party of Struggle make the process of recruiting candidates for regional heads in North Minahasa Regency in accordance with the guidelines and mechanisms mandated the Central Executive Board